(3GdMOhO (B( (3GdadcjI (B)s
(3ChdgG (B:s
(3GdMeO GdJGQjN (B: (3jhe eYdhe jfSH Edjg ReGf jCJi Ydjg GdOGFQI (B: (3SWM jMjW Hg NW hGMO , ai OGNd cd GdNWhW GdeSJbjeI GdNGQLjI ef Jdc GdfbWI Edi GdeMjW eG jSGhjg s
(3BNQgG (B:s
(3agh bWQ GdXd GdeYOd HMSH HYO GdTeS CjVkG ef GdCQV hSW GdbeQ hNGUI eSjQ jhe MJi fhGai jhe GdSGOS ef GdTgQ cPdc faYd HGdHhGbj HYO eSjQ jhe fRjOg Ydi cd LfS MJi fhGaj hfHdZ GdeQGO Je GdMOhO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3cJHJ Hbde bdjd GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs